Estudo da influência da variação do diâmetro do agregado graúdo na anisotropia do concreto - (:unkn) unknown (Universidade Federal do Pampa, 2021)
Concrete is the most used structural material in civil construction. For this reason, having a good knowledge of their properties and characteristics becomes of great importance, especially for ensuring the safety of structures. In this line of thought, this research seeks to study the influence of the maximum dimension of the coarse aggregate on the degree of anisotropy of the concrete. For this, cylindrical and cubic specimens were produced with concrete of the same mass and w/c ratio, varying only the maximum dimension of the coarse aggregate. Three (3) types of concrete were produced, the concrete being called C0, produced with 0 gravel and C1 and C2 concretes with 1 and 2 gravel, respectively. At 28 days of age, the specimens were subjected to mechanical tests of Axial Compression and Traction by Diametral Compression. The concrete strengths were obtained for a load imposed in the direction perpendicular to the direction of molding and compaction and for a load imposed in the direction parallel to the molding and compaction of the concrete. The obtained results pointed to a decrease in the indirect tensile strength and axial compression when applying a load on the faces perpendicular to the casting and densification direction of the concrete. The indication of the influence of the maximum dimension of the coarse aggregate could be observed in concretes when the strengths decreased as the maximum dimension of the coarse aggregate increased.
Keywords: Engenharia civil; Concreto; Anisotropia; Dimensão máxima do agregado; Tração por compressão diametral; Compressão axial; Civil engineering; Concrete; Anisotropy; Maximum aggregate dimension; Traction by diametral compression; Axial compression; CNPQ::ENGENHARIAS